Overlooked and Invisible: Everyday Experiences of Microaggressions for LGBTQ Adolescents. Issue 10 (24th August 2019) - Munro, Lauren; Travers, Robb; Woodford, Michael R.
ABSTRACT: Lesbian, gay, bisexual, transgender, and queer (LGBTQ) adolescents face a number of challenges in their lives related to heterosexism and cissexism. Drawing on the microaggressions framework, we conducted two focus groups with LGBTQ adolescents ( n = 11; ages 14–18, six trans/genderfluid, one person of color) to (1) explore the type and nature of microaggressions experienced by LGBTQ adolescents; (2) assess the relevance of existing LGBTQ microaggression taxonomies for this group; and (3) understand the impact of microaggressions on LGBTQ adolescents. Participants' experiences of microaggressions reflected complex forms of discrimination emerging from the intersections of sexual and gender identity.